Turning carbon dioxide into fuel concomitantly to the photoanode-driven process of organic pollutant degradation by photoelectrocatalysis - Brito, Juliana Ferreira de [UNESP]; Perini, João Angelo Lima [UNESP]; Perathoner, Siglinda; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2019)
TiO 2 nanotubes (TiO 2 Nt) were modified with zirconium oxide and used as photoanode-driven to oxidize benzyl alcohol concomitantly to the reduction of carbon dioxide using a gas diffusion layer modified with cuprous oxide (GDL-Cu 2 O) as cathode. ZrO 2 was deposited by a simple wet chemical method onto TiO 2 Nt and presented higher photocurrents when irradiated by UV–Vis irradiation. Under optimized conditions, 0.1 mol L −1 Na 2 SO 4 pH 7 and 0.1 mol L −1 KHCO 3 pH 7 supporting electrolytes in the anodic and cathodic compartments, respectively, the degradation of benzyl alcohol reached 41% at the TiO 2 Nt electrode and 68% at TiO 2 Nt-ZrO 2 under UV–Vis irradiation and bias potential of 1.5 V vs. Ag/AgCl. Concomitantly, the electrons driven to the cathode side saturated with CO 2 promoted generation of around 3.8 mmol L −1 of methanol and 0.96 mmol L −1 of ethanol under TiO 2 Nt-ZrO 2 . So, our finding shows for the first time the performance of a hybrid reactor in which is possible to promote photooxidation of an organic compound concomitantly to CO 2 reduction to alcohol using a simple photoanode-driven and a cathode separated by a proton exchange membrane.
Keywords: Alcohol production; CO 2 reduction; PEC reactor; Semiconductors; Wastewater oxidation